Buku Interaktif Sebagai Media Komunikasi Pengenalan Tari Gending Sriwijaya Untuk Anak Usia 6-12 Tahun Di Kota Palembang - Sofiah Ceria; Didiek Prasetya; Hestia Rachmat Nunciata (VisArt: Jurnal Seni Rupa dan Design, 2025)
Gending Sriwijaya Dance is one of the intangible cultural heritages of South Sumatra, rich in meaning and historical value. However, a lack of interest and the absence of engaging and age-appropriate media have led to a decline in the introduction of this traditional dance to younger generations. This design project aims to introduce the Gending Sriwijaya Dance to children aged 6-12 in Palembang through an interactive children’s storybook. The methods used include observation, interviews with elementary school students, and literature studies to explore appropriate content and visual approaches. The book is designed with expressive illustrations, easy-to-understand narratives, and interactive activities that can stimulate children's interest in local culture. The resulting book is expected to serve as an enjoyable alternative medium to help introduce and instill a love for regional culture from an early age, as well as a part of cultural preservation strategies through a visual approach that is adaptive to the times and children’s developmental needs